Pemanfaatan Aplikasi e-Commerce dan Media Sosial sebagai Penunjang Pemasaran Produk UMKM di masa pandemi covid-19 - Muhammad Resha (ADPERTISI, 2022)
The current Covid-19 pandemic is still endemic throughout the world and has an impact on all sectors including the economy. MSME actors in Indonesia are among the most affected, namely the slowdown in the economic sector which makes Micro, Small and Medium Enterprises (MSMEs) experience a significant setback. In accordance with the analysis and discussion, it can be concluded that Micro, Small and Medium Enterprises (SMEs) in the village of Taeng, Gowa Regency, after the counseling and assistance have had enthusiasm and hope during this pandemic. Residents become more aware of the benefits of e-Commerce and Social Media Applications as Supporting MSME Product Marketing in Taeng Village, Gowa Regency. From the results of discussions with participants, the advice given to MSME participants in utilizing social media and e-commerce is to register their MSMEs to the facility. After that, they started to promote their products and continued to consistently take advantage of existing facilities